Peace journalism and framing in the Northern Rakhine State of Myanmar - Myint, Zin Mar (Kansas State University, 2017)
The country of Myanmar started political reforms in 2010. Along with the process of becoming more democratic, peace and reconciliation have become very important due to the decades-long civil wars that continue to rage between ethnic minority groups and Myanmar Army. The Myanmar media have the potential to play a huge role in national reconciliation. One conflict between the Muslim and the Buddhist of Rakhine State of Myanmar has gained international attention. Research shows that media play a destructive or constructive role in conflict resolution depending on which news frames they adopt in reporting. This uses the theoretic peace journalism perspective, in which media take a careful, consistent and conscientious approach to report stories that create opportunities for society at large and emphasizes non-violent responses to conflict (Lynch, 2008). Using mass media framing theory and existing peace journalism literature, this study investigates the prominence of war and peace journalism framing in the media coverage of an ongoing conflict in the Northern Rakhine State of Myanmar between a group of Muslims and Buddhists who inhabit the region. This study employed a comparative analysis to examine war and peace journalism frames from stories published in four newspapers; two from Myanmar, one from Bangladesh, and one from the U.S. The analysis was guided by Galtung’s (1986) classifications of peace and war journalism and operational definitions derived by Lee and Maslog (2005). Findings suggest that war journalism frames are dominant in the coverage of the Rakhine conflict regardless of media origin. Even though not statistically significant, the government-run newspaper from Myanmar was revealed to produce more peace journalism stories than the other three newspapers. There was a slight difference in coverage of the conflict between English-language and Burmese-language newspapers in terms of peace/war journalism framing. English news stories were more likely to be framed as war journalism than peace journalism. In addition, news stories produced by U.S. journalists and foreign news wire services such as the Associated Press and Reuters were more war-dominant than stories produced by local/regional journalists of Myanmar and Bangladesh. This study calls for international and local journalists to reevaluate their current conflict reporting practices to promote their positive roles in peace processes.
Keywords: Peace journalism; Framing theory; Media frames; Myanmar; Rakhine; Bangladesh